Effective factors and issues in online learning in Covid-19: a global review - Jahanaray, Ali; Jahanaray, Mohammad; Zohoorian, Zahra (EDUCATIO : Journal of Education, 2022)
The unexpected outbreak of covid-19 caused education centers to halt their physical classes and rashly switch to online classes. This review paper has as its primary objective identifying related issues faced by different countries and comparing them to get a global overview, and debating whether the dissemination of Covid-19 has adversely affected the educational process in different countries the same way or not. Internet connection, lack of technological devices, deficiency in ICT competencies, and insufficient power supply are reported by most African, South American, and Asian countries as their significant issues. Mental health issues, concerns for future jobs, and discrimination among students are reported as significant issues in North America. Lack of teacher/student training, inaccessibility to stable internet connections, and digital devices are the main problems for European countries. The other reason behind this review is to find out the most significant factors in computing an effective online learning experience. In this sense, four factors are acknowledged in this paper as influential factors in online learning classes. This review found out that in undeveloped countries success of online education is highly correlated with the financial status of countries, whereas, in developed countries, its success has other areas of concern among people.